KERJA SAMA SISTER CITY ANTARA KOTA BANDUNG DENGAN KOTA KAWASAKI DALAM BIDANG LINGKUNGAN HIDUP PADA TAHUN 2017-2020 - Nur Asyifa Salsabila Siregar (2022)
This research discusses the cooperation conducted by Bandung City, Indonesia with Kawasaki City, Kanagawa Prefecture, Japan within the framework of sister city cooperation in the environmental sector in 2017-2020. The sister city cooperation between Bandung City and Kawasaki City is a cooperation between the city governments aimed at improving bilateral relations between the two cities, which focuses on cooperation in waste management and environmental problems in Bandung City. This study discusses the sister city cooperation between Bandung and Kawasaki in the environmental sector by using descriptive qualitative methods and also using interview and literature studies research techniques to answer the research question. In analyzing this research, the author also uses the theory or concept of city diplomacy and sister city. The results of this research explain that this cooperation provides a good contribution in the form of increasing the capacity of Bandung City's human resources as well as improving the management and handling of waste problems. This research also explains that the cooperation has encountered some obstacles related to funding, the COVID-19 pandemic, communication process and dominance of training implementation compared to infrastructure development. Keywords: Bandung City, Cooperation, Environment, Kawasaki City, Sister City